Aloe vera Leaf Anti Inflamation's Activity Speeds Up the Healing Proccess of Oral Mucosa Ulceration - Agoeng Tjahajani; Widurini Djohan (Faculty of Dentistry, Universitas Indonesia, 2013)
Previous work showed that 25% of inner layer Aloe vera leaf extract was effective as anti-inflammatory on the oral mucous of Wistar rats. Objective: The aim of this study was to examine the lowest concentration of whole leaf Aloe vera extract that could accelerate healing process of ulceration on rats. Methods: Sixty inbreeding Spraque Dawley rats was exposed to solution of Hydrogen Peroxide 10% during three days to induced inflammation on the labial mucous inferior of rats. During the next three days, on the same area of control group were topically applied solution of Natrium Chloride 0.9%; while in the treatment group were topically applied 6.25%; 12.5%; 25% of whole leaf of Aloe vera extract for 3x5 minutes with 90 minutes intervals. On the fourth day, five rats in each group were sacrificed; and the same treatment was done on others groups. On the sixth day, five rats of each group were sacrificed; and the same treatment was done on the rest group up to seven days. On the eighth days, the rest groups were sacrificed. Microscopic slides were done. Results: Microscopic slides were analyzed under light microscope and scored. Statistical analysis with Mann-Whitney test showed significant differences between control and treatment group (p<0.05). Conclusion: Application of 6.25% whole leaf Aloe vera extract was the lowest and the most effective concentration in accelerating the healing process of oral mucous ulceration on rats. DOI: 10.14693/jdi.v18i1.56